UNIVERSITY OF ECONOMICS IN SUSTAINABLE DEVELOPMENT OF A REGION - Olga V. Molchanova (Высшее образование в России)
The article suggests that vocational education is a strategic priority and a catalyst for the development of a region in complex socio-demographic conditions. Only immensely innovative transformations in the field of education and the orientation towards cooperation between the universities and the state, business, and other universities can in recent conditions ensure sustainable development.